Perilaku Makan Badak Sumatera di Suaka Rhino Sumatera, Taman Nasional Way Kambas, Lampung - Suharto, Ignatius; Rustiati, Elly Lestari; Adi, Marcelus (Universitas Atma Jaya Yogyakarta, 2007)
Research on the feeding behaviour, feeding plants and the way to access the plants has been conducted on Sumateran rhinos at and in collaboraton with Sumatran Rhino Sanctuary, Way Kambas National Park, Lampung, by scanning and rapid assessment methods. Feeding activity is done during day time, especially in the morning (05.00-10.00) and in the afternoon (14.00-18.00). Plants consumed include saplings (42%), followed by trees (30%), seedlings (20%) and liana (8%). Cutting (86%) is the most common way to access the food sources, followed by pulling (9%), pushing by its head and holding in between front legs (4%) and twisting by its horn (1%).